PROFESSIONAL DEVELOPMENT OF A FOREIGN LANGUAGE TEACHER AT UNIVERSITY: COMPETENCE AND CREATIVITY ASPECTS - Alla Durdas (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article deals with the issues of development of foreign language teachers' competences and creativity at university. The necessity to constantly develop professional competences of a foreign language teacher has been substantiated; the lack of research on a foreign language teacher's creativity in scientific literature has been stressed. The connection of creative teaching with emotions has been revealed. Emotions at foreign language lessons have been specified as a factor affecting students' academic outcomes, interest, commitment and personality development. The ability of emotions to affect the social atmosphere of a classroom and learning environments has been admitted. Teachers' creativity and teaching effectiveness have been defined as two essential elements of teaching. The article says that foreign language teachers' professional competences can be developed both in a formal way - through participation in improvement proposals offered by various institutions, and in an informal way: reading specialized literature or meetings with other teachers of a given training discipline for exchanging professional experience. A STRIDE technique has been suggested for leading a teacher through a process of reflection using a six-step focused analysis, which helps teachers to understand both their strengths and the problem areas as well as to make them notice potential ways of reaching their goals.